2020
DOI: 10.1021/acsami.0c11534
|View full text |Cite
|
Sign up to set email alerts
|

Back-Channel Defect Termination by Sulfur for p-Channel Cu2O Thin-Film Transistors

Abstract: The absence of a high-performance p-channel oxide thin-film transistor (TFT) is the major challenge faced in the current oxide semiconductor device technology. Simple solution-based back-channel subgap defect termination using sulfur was developed for p-channel cuprous oxide (Cu2O)-TFTs. We investigated the origin of poor device characteristics in conventional Cu2O-TFTs and clarified that it was mainly because of a back-channel donor-like defect of ∼2.8 ×1013 cm–2 eV–1, which originated from the interstitial C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…On the other hand, V o is also energetically stable point defect but electrically inactive defect for Cu 2 O channel [122,123]. Therefore, amphoteric Cu interstitial defect (Cu i ) is considered to have a large responsibility for the poor device performance of Cu 2 O-TFT [115,124].…”
Section: All-oxide-tft-based Cmos Invertermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, V o is also energetically stable point defect but electrically inactive defect for Cu 2 O channel [122,123]. Therefore, amphoteric Cu interstitial defect (Cu i ) is considered to have a large responsibility for the poor device performance of Cu 2 O-TFT [115,124].…”
Section: All-oxide-tft-based Cmos Invertermentioning
confidence: 99%
“…By reducing the back-channel Cu i defect originating from the formation of CuSO 4 back-channel layer (Figure 7(b)), significant improvements of the off-current down to as low as ∼ 1 pA and s-value are observed. The simple back-channel defect termination using Thiourea solution offers the improved Cu 2 O-TFTs exhibiting the mobility of ∼ 1.81 cm 2 /Vs, s-values of ∼ 1.3 V/dec., and the on/off current ratio of ∼ 6.0 × 10 6 .1 [115]. Min et al [111] also demonstrated the improvement of Cu 2 O-TFT performances by forming CuO back-channel layer and obtained field-effect mobility of ∼ 0.75 cm 2 /Vs, svalues of ∼ 0.11 V/decade, and the on/off current ratio of ∼ 2.81 × 10 8 .…”
Section: All-oxide-tft-based Cmos Invertermentioning
confidence: 99%
“…Furthermore, the CMOS inverters using n‐channel IGZO and p‐channel Cu X O with the PCL showed the voltage gain of 14 at supply voltage (V DD ) of 20 V. Chang et al examined the effect of back‐surface‐derived defects on the electrical characteristics of Cu 2 O TFTs. [ 31 ] The donor‐like defects originate from the interstitial Cu (Cu i ) defect, which can be effectively reduced with sulfur (S) ion treatment. The S ion treatment assists the chemical reaction of Cu i with S and O ions, facilitating the formation of a thin CuSO 4 passivation layer on top of the Cu 2 O layer (Figure 3e,f).…”
Section: Progress Of P‐channel Oxide Thin‐film Transistorsmentioning
confidence: 99%
“…The poor electrical performances of Cu2O TFTs was attributed to a high density of defects at grain boundaries and at the semiconductor/dielectric interface, e.g., VOs and CuO secondary phase [21]. Several strategies are proposed to control these defects and to improve the performance and stability of Cu2O TFTs, including surface passivating [22,23], doping [24], using high-κ gate dielectrics (Al2O3, HfO2) [6]. For example, Chang and Nomura et al recently demonstrated the use of sulfur to reduce back-channel defect of p-type CuxO TFTs and achieved μsat of 1.38 cm 2 /Vs and on/off ratio of 4.1 × 10 6 [21].…”
Section: Cu2o Based Devicesmentioning
confidence: 99%